THE CHANGING SENSE OF POLITENESS IN FEMALE CHARACTERS IN MARGARET MITCHELL'S GONE WITH THE WIND - Rendra Bening Prakoso (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
Sense of politeness in language is an important aspect in human interaction. Since it is dealing with society,this makes politeness something flexible based on place and time. It means that what is meant by word "polite" is different from one place to another place or even politeness in a particular area changes from time to time. One of literary works that gives a clear description about a society including sense of politeness is Margaret Mitchell's story of the Old South Gone With the Wind. Though it is an old story we still are able to learn something from it about sense of politeness. Gone With the Wind novel took old southern United States society in American civil war era (1861-1865) as the setting of the story, which still adopted patriarchy system. This society had a tendency to clearly polarize men and women's role in the family and society, in which the women should be kind, polite, and gracious. While on the other hand, men, who held the superior position in the society. could express their feeling more freely. This politeness changes when the Civil War comes through this process, there are many changes in the society that influence the rapport. From the beginning when women must speak soft, gracious, and, politely, until the coming of the war, in which they have to leave all their old status as the inferior people. And the last is when the men returned back to their family.